A comparative study of the actions of alkylpyridinium salts from a marine sponge and related synthetic compounds in rat cultured hippocampal neurones - Koss, David J (BioMed Central, 2007)
BACKGROUND: Polymeric alkylpyridinium salts (poly-APS), are chemical defences produced by marine sponges including Reniera sarai. Poly-APS have previously been shown to effectively deliver macromolecules into cells. The efficiency of this closely follows the ability of poly-APS to form transient pores in membranes, providing strong support for a pore-based delivery mechanism. Recently, water soluble compounds have been synthesised that are structurally related to the natural polymers but bear a different number of pyridinium units. These compounds may share a number of bio-activities with poly-APS. Using electrophysiology, calcium imaging and 1,6-diphenyl-1,3,5-hexatriene imaging, the pore forming properties of poly-APS and four related synthetic oligomers have been tested on primary cultured rat hippocampal neurones. RESULTS: Acute application of poly-APS (0.5 μg/ml), reduced membrane potential, input resistance and suppressed action potential firing. Poly-APS evoked inward cation currents with linear current-voltage relationships similar to actions of pore formers on other cell types. Poly-APS (0.005–5 μg/ml) also produced Ca(2+ )transients in ~41% of neurones. The dose-dependence of poly-APS actions were complex, such that at 0.05 μg/ml and 5 μg/ml poly-APS produced varying magnitudes of membrane permeability depending on the order of application. Data from surface plasmon resonance analysis suggested accumulation of poly-APS in membranes and subsequent enhanced poly-APS binding. Even at 10–100 fold higher concentrations, none of the synthetic compounds produced changes in electrophysiological characteristics of the same magnitude as poly-APS. Of the synthetic oligomers tested compounds 1 (monomeric) and tetrameric 4 (5–50 μg/ml) induced small transient currents and 3 (trimeric) and 4 (tetrameric) produced significant Ca(2+ )transients in hippocampal neurones. CONCLUSION: Poly-APS induced pore formation in hippocampal neurones and such pores were transient, with neurones recovering from exposure to these polymers. Synthetic structurally related oligomers were not potent pore formers when compared to poly-APS and affected a smaller percentage of the hippocampal neurone population. Poly-APS may have potential as agents for macromolecular delivery into CNS neurones however; the smaller synthetic oligomers tested in this study show little potential for such use. This comparative analysis indicated that the level of polymerisation giving rise to the supermolecular structure in the natural compounds, is likely to be responsible for the activity here reported.